1315Influence of comorbidity on mortality in patients with Rheumatoid Arthritis 1980-2015: A longitudinal population-based study. (2nd September 2021) - Almutairi, Khalid; Nossent, Johannes; Preen, David; Keen, Helen; Inderjeeth, Charles
Abstract: Background: To describe temporal changes in mortality rates for patients with Rheumatoid arthritis (RA) in relation to comorbidity accrual from 1980-2015 in Western Australia (WA). Methods: Using population-level linked data from WA health administrative datasets (hospital morbidity, emergency department and death data) we followed 17, 125 RA patients (ICD-10-AM M05.00–M06.99, ICD-9-CM 714) from 1980- 2015. Comorbidity was ascertained using the Charlson Comorbidity Index (CCI). Mortality rate ratios (MRR) were calculated per decade between the RA cohort and the WA general population by direct age standardisation method, Results: During 356, 069 patient-years, a total of 8955 (52%) deaths occurred in the RA cohort. The highest prevalence of comorbidity (688.6 per 1000 separations) was in the period 1991-2000 following a 1.3% average annual increase since 1980. In-hospital mortality rate was highest (26.7 deaths per 1000 separations) in the same period. After 2001, both RA comorbidity and mortality rates decreased annually by -0.5% and -4.8%, respectively, with annual changes of -4.4% to -2% and from 2011-2015, respectively. The overall mortality rate in RA patients after age adjustment was 2.5-times (95%CI: 2.52-2.65) higher than the general population between 1980-2015 and 1.5-times (95%CI: 1.39-1.81) for 2011-2015. Conclusions: The annual comorbidity prevalence and mortality rates in WA have decreased significantly since 2001 reflecting improvements in the management of RA and comorbidity. Key messages: The mortality rate in Rheumatoid Arthritis patients in Western Australia remains 1.5-times higher than their community.